Analisis Strategi Komunikasi Pemasaran Asuransi Syariah pada Asuransi Jiwa Bumiputera Syariah - Amina Fitri Siregar; Rahmi Syahriza (Universitas Labuhanbatu, 2022)
This article aims to provide an understanding of the analysis of sharia insurance marketing communication strategies for sharia-based Bumiputera life insurance which includes communication. Sharia insurance is one of the institutions that facilitates facilities in the service sector, appearing in a group environment which is especially broadly in a state of lack of understanding about sharia insurance and its implementation. This incident has an impact on people who are still reluctant to use insurance services with a sharia identity, even though they hope to ease the burden on people who are affected by unexpected disasters by using a way to transfer the risks that will be faced by providing premiums. money presented in the policy in the form of products. Bumiputera Syariah Life Insurance. In offering its products, PT Asuransi Jiwa Syariah Bumiputera implements a strategy that is contrary to other companies to increase its product marketing, namely by conducting socialization to the public about sharia insurance products. IBased on these problems, the formulation of the problem in this study is to explain how the Analysis of Islamic Insurance Marketing Communication Strategy on Bumiputera Syariah Insurance products. Therefore, the hope of this research is to find out how the strategy in product marketing used by PT. Bumiputera Syariah Life Insurance in advancing the marketing of insurance products. This study uses a qualitative method by using the method of collecting materials used is a question and answer system and taking pictures. A descriptive qualitative description in the form of vocabulary, works or talks from people who behave and are easy to understand. Descriptive study is used to analyze and describe the existing expressions because it uses a deductive reasoning process.